The Role Of Parents In Overcoming Juvenile Delinquency In Bah Butong Village - Mutiara Salsabila; Mahyuni Harahap; Nurdelita Anggraini; Salsabila As – Syifa; Nefi Darmayanti (Sean Institute, 2024)
Adolescence is a time when a child currently is at in search teak himself, wants know Who himself actually. A child it is said teenagers, if He Already until age 17 years. At the age of this, a child experiencing a period called puberty. During puberty, usually child want to try all something new in his life, appeared various type turmoil emotions, and many arise problem Good in family and also environment social. In overcoming the occurrence socializing free for teenagers one of them can seen from Environment the most important and first family that is responsible answer on effort overcome mischief teenager That alone and not seldom teenagers are very easy affected with things new without think long whether That Correct or wrong, thing this is also possible cause mischief teenagers. The method used in study This is study field is an approach that involves direct data collection from environment or relevant location with Topic study. That when mischief teenager overwrite a family so parents ' efforts in overcome mischief teenager need stage a coaching through Islamic religious teachings aimed at them become teenager a good, pious generation or pious, faithful, knowledgeable and devout, for to build teenager That Can done through various approach like efforts made by parents yourself and your environment surrounding area.